2023
DOI: 10.3390/s23031091
|View full text |Cite
|
Sign up to set email alerts
|

An Ultracompact Angular Displacement Sensor Based on the Talbot Effect of Optical Microgratings

Abstract: Here, we report an ultracompact angular displacement sensor based on the Talbot effect of optical microgratings. Periodic Talbot interference patterns were obtained behind an upper optical grating. By putting another grating within the Talbot region, the total transmission of the two-grating structure was found to be approximatively in a linear relationship with the relative pitch angle between the two gratings, which was explained by a transversal shift of the Talbot interference patterns. The influence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Assuming that G1 and G2 have a relative displacement, the complex amplitude distribution behind G2 can be given [25] as follows:…”
Section: Principlementioning
confidence: 99%
See 1 more Smart Citation
“…Assuming that G1 and G2 have a relative displacement, the complex amplitude distribution behind G2 can be given [25] as follows:…”
Section: Principlementioning
confidence: 99%
“…In 2006, A. Wang et al reported a sensor that used the self-imaging effect to detect the local intensity and incident angle of light [24]. In 2022, Z. Yang et al reported an ultracompact angular displacement sensor using a double-grating structure with a sensitivity of 0.19 mV/arcsec within a range of ±396 arcsec [25]. Since both the linear and angular displacements are synchronously changing the amplitude of the output signal or the patterns of the selfimaging images in the cases mentioned above, the linear and angular displacements are hard to distinguish from each other.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that G1 and G2 have a relative displacement, the complex amplitude distribution behind G2 can be given [25] ( ) ( ) ( )…”
Section: Principlementioning
confidence: 99%
“…In 2006, A. Wang et al reported a sensor that used the self-imaging effect to detect the local intensity and incident angle of light [24]. In 2022, Z. Yang et al reported an ultracompact angular displacement sensor using a double-grating structure with a sensitivity of 0.19mV/arcsec within a range of ± 396arcsec [25]. Since both the linear and angular displacement synchronously changing the amplitude of the output signal or the patterns of the self-imaging images in the cases mentioned above, the linear and angular displacement is hard to be distinguished from each other.…”
Section: Introductionmentioning
confidence: 99%